One activity to reflect about sex - Bujold, Francine; Dionne, Jacques; Lapointe, Claire (Paidéia (Ribeirão Preto), 2000)
In this paper, it is intended to describe the characteristics of an adolescents sample living in institutions, their problems, and the concepts behind the program proposed, based on a reorganization of activities. In a second phase it is explained the way the information about sex begin to be transmitted, the orientation to talk about this subject, specially the experiences the adolescents had and the opportunity to reflect; the activity about sexual education included to form a group to help the adolescents that had been abused.